2006
DOI: 10.1007/bf03021846
|View full text |Cite
|
Sign up to set email alerts
|

Review article: The role of anticonvulsant drugs in postoperative pain management: a bench-to-bedside perspective

Abstract: Purpose: Anticonvulsant drugs are effective in the treatment of chronic neuropathic pain but were not, until recently, thought to be useful in more acute conditions such as postoperative pain. However, similar to nerve injury, surgical tissue injury is known to produce neuroplastic changes leading to spinal sensitization and the expression of stimulus-evoked hyperalgesia and allodynia. Pharmacological effects of anticonvulsant drugs which may be important in the modulation of these postoperative neural changes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
16
0

Year Published

2006
2006
2017
2017

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 45 publications
(17 citation statements)
references
References 98 publications
1
16
0
Order By: Relevance
“…Generally our data on PONV incidence are in accordance with those of Seib et al [83] and Hurley et al [81] meta-analysis and in discordance with the other authors who described a significant reduction of nausea and vomiting [79,80,82,84,85]. Meanwhile, the information reported from the other systematic-narrative reviews regarding PONV are inconclusive [11,28,77,78] Furthermore, it would be considered that RCTs included in the previous reviews and those included in the present one are partially different.…”
Section: Patients Includedsupporting
confidence: 75%
See 1 more Smart Citation
“…Generally our data on PONV incidence are in accordance with those of Seib et al [83] and Hurley et al [81] meta-analysis and in discordance with the other authors who described a significant reduction of nausea and vomiting [79,80,82,84,85]. Meanwhile, the information reported from the other systematic-narrative reviews regarding PONV are inconclusive [11,28,77,78] Furthermore, it would be considered that RCTs included in the previous reviews and those included in the present one are partially different.…”
Section: Patients Includedsupporting
confidence: 75%
“…The first studies of PGL use after major surgery pain management were published in 2006 and furthermore previous systematic narrative [11,28,77,78] or meta-analytic [79][80][81][82][83][84][85] reviews reported data from GBP clinical trials until 2006 (included). A total of three trials on PGL use for post-operative pain management [30,69,71] have been included in only one review [11] and the other three [77][78][79] included only one trial on postoperative dental pain published in 2001 [30]. Thus, we decided to take in consideration only recent (from 2006-2009) RCTs which investigated the analgesic effects of GBP or PGL in adult patients (age range 18 years and above) underwent to surgical procedures.…”
Section: The Selection Of the Studiesmentioning
confidence: 99%
“…Other trials also suggest the potential analgesic efficacy of other anticonvulsant drugs including pregabalin, lamotrigine and possibly oxcarbazepine. 20 This was also confirmed in a recent meta-analysis by Seib and Paul 23 showing that gabapentin given preoperatively decreased pain scores and analgesic consumption in the first 24 hr after surgery. However, the clinical significance of this finding has yet to be determined.…”
Section: Anticonvulsantsmentioning
confidence: 58%
“…22 Gabapentin is a 3-alkylated analogue of gamma-amino butyric acid (GABA) that has been shown to be effective in reducing pain scores and opioid consumption in a number of surgical settings. [23][24][25][26] Also, when used in combination with a COX-2 inhibitor, gabapentin has been shown to have specific efficacy in reducing pain evoked by movement and respiration after surgery. 9 Furthermore, gabapentin, both alone and in combination with a COX-2 inhibitor, led to improvement in indices of pulmonary function during the recovery period after abdominal surgery.…”
Section: Discussionmentioning
confidence: 99%